Description of Students' Mathematical Problem Solving Ability on Flat Build Material Based on Gender Class VIII Mts Ar-Rahman Kaju - Apriansyah, Ahmad; Trisnowali MS, Andi; Sirwanti, Sirwanti; Iswandy, Iswandy (JUPE : Jurnal Pendidikan Mandala, 2024)
This research is a qualitative research with a descriptive approach which aims to determine the description of students' mathematical problem solving abilities in flat shapes material based on Gender Class VIII MTs Ar-Rahman Kaju which is arranged based on indicators of problem solving abilities, namely indicators of understanding problems, planning solutions, resolving problems and examining return. The data obtained is the result of interviews with 2 male students and 2 female students. The data collection methods used were observation, interviews and problem solving ability tests. The results in this study show that female students are better at solving mathematics problems than male students. It can be seen from this research that female students completed all four indicators of mathematical problem solving ability, while male students were only able to complete two of the indicators of mathematical problem solving ability.